Penelitian Kualitatif : komunikasi, ekonomi, kebijakan publik, dan ilmu sosial lainnya - H.M. Burhan Bungin (Kencana, 2007)
ws.c.1-5/ir,c.6-7/oen, .08/ws.c.9-11/nr, c.12-15/stoc6, c.1-2, 4-5; 7-10,12/stc13,c.13/ws.c.16-17